Morphometric assessment of the canine hip joint using the acetabular angle of retrotorsion - Doskarova, B; Kyllar, M; Paral, V (Veterinary and comparative orthopaedics and traumatology, 2010)
Morphometric assessment of the canine hip joint using acetabular angle of retrotorsion was used in this study. The aim of our study was to compare the acetabular angle of retrotorsion (AAR) with values of the Norberg angle (NA) and the hip score (HS) in the Leonberger dog breed and to determine the cut-off point of AAR that distinguish between normal and dysplastic hip status on the basis of Fédération Cynologique Internationale (FCI) hip evaluation. Retrospective analysis of NA and AAR was measured from standard ventrodorsal pelvic radiographs with extended femurs in 387 Leonberger dogs (141 males and 246 females) from 18 to 63 months of age, which were then divided into five age-groups. Through analysis of these radiographs, it was determined that the cut-off point for NA was 105°, AAR was 15°, and the acetabular angle of retrotorsion was positively correlated with Norberg angle and negatively correlated with hip score. The results of our study indicate that the acetabular angle of retrotorsion may represent a reliable morphometric assessment tool in evaluating acetabular cup conformation, and values of AAR may help to assess the FCI grade of canine hip dysplasia.
Keywords: psi; femur; pohlavní dimorfismus; dysplazie kyčelního kloubu u psů; acetabulum; Hip Joint; Animals; Femur; Acetabulum; mužské pohlaví; Dogs; radiografie; Hip Dysplasia, Canine; Male; zvířata; Radiography; Sex Characteristics; kyčelní kloub